Pengaruh Penambahan Admixture Terhadap Kuat Tekan Beton Dari Berbagai Merek Semen - Fitrawansyah, Dian; Lakawa, Irwan; Sulaiman, Sulaiman (Sultra Civil Engineering Journal (SCiEJ), 2020)
Tonasa cement, Bosowa cement, and Tiga Roda cement have diffenrence characteristic from procedure to produce and composition of ingredients, the difference are probably reach the diffenrence respond or effected from three brands are mixed from admixture to be a mix concrete. One of the commonly admixture and easy to find is Damdex Brand that can increase the strengthness of the concrete. The aimed of this investigation to analyse the effect of admixture (Damdex) variation toward concrete compressive strength by comparison the cement brands.The methodology of this investigation is experiment method or material test in laboratory. The concrete compressive strength will calculated during 28 days age, after giving an admixture (0%,1%, 1,5%,2%, 2,5% dan 3%) with different brands cement variation,but composition of Concrete such Agregat and Water are same from each treatment. The sample from each treatment totally 3 tested samples. The result of this investigation, Tonasa cement is increase with concrete compressive strength from highest of admixture (Damdex) from admixture level is 2% which gain compressive strength 385,24 Kg/cm2 or increasing amount 23,52% from normal concrete compressive strength. Bosowa brand is increase with concrete compressive strength from the highest admixture ( Damdex) the level is 2.5 % with compressive strength gain is 338,00 Kg/cm2 or increase amount 10,15% from Normal concrete compressive strength.Compressive strength of Tiga Roda brand also gain increase from admixture with highest level is 3% which 354,35 Kg/cm2 compressive or increase amount 18,60% from normal concrete compressive strength